Effect of binders on 500mg metformin hydrochloride tablets produced by wet granulation - L.C. Block; L.O. Schmeling; A.G. Couto; M.A.S. Silva; M.P. Tagliari; T.M.B. Bresolin; S.C. Mourão (São Paulo State University (UNESP), 2009)
Metformin hydrochloride (MH) is an oral hypoglycemic agent and a high-dose drug that has poor flow and compression properties. In this study, the feasibility of developing adequate, low cost 500mg tablets of metformin hydrochloride by wet granulation was tested with several binders (Starch / PVP K30®; Starch 1500® /PVP K30®, PVP K30® and PVP K90®) in a simple tablet press of the type used in small pharmaceutical laboratories. The drug powder was tested for ability to flow, by determining Carr's Index (CI) and the Hausner ratio (HR). Differential scanning calorimetry and thermogravimetric analysis were carried out on isolated MH and 1:1 (w/w) binary mixtures with the excipients. The size distribution, friability, flow properties and drug content of the granules were analyzed, as were the hardness, friability, disintegration, dissolution and uniformity of the dosage form. The drug powder showed CI > 22% and HR > 1.25, characteristic of a poor flow powder, and no significant incompatibilities with the excipients. All the granules showed adequate flow properties and were suitable for pressing into tablets, all of which complied with pharmacopeial specifications. The starch /PVP K30® and starch 1500® /PVP K30® mixtures were best for producing 500 mg MH tablets.